The Reality of Adopting Organizational Culture Approach at King Abdullah University Hospital in Jorden - Al-Jammal, Hamdan Rasheed; Al-Khasawneh, Akif Lutfi; Methani, Bilal (International Journal of Advances in Management and Economics, 2018)
This study aimed at identifying the reality of adopting organizational culture approach at King Abdullah University Hospital through defining some elements of organizational culture approach including (values, beliefs, anticipations, customs, prohibitions, rituals, characters, laws, and regulations). Population of the study was consisted of all employees of central executive management and the questionnaire was designed for data collection. A random sample reached to (160) employees was used. The questionnaires were delivered directly by the hand and received in the same way. They were statically analyzed. The study has reached for following results: the employees shall comply for legislative values in the organization, adopt the organizational believes, commit with laws and regulations of the organization, speak about contrabands in the organization, and create rituals and common relations among the employees of organization. It has been recommended in following suggestions: management has to deal with all employees equally were they are compiled by the most organizational values at organization. It also must share the employees in the process of managerial decision- making in order to increase percentage of employees' adopting organizational believes at organization. The necessity to improve the organizational environment at hospital to be reflected in assessing common organizational culture among employees. Keywords: Organizational culture, Values, beliefs, Anticipants and customs, Contrabands, Characters, laws, Regulations.